A clearing in the objectivity of aesthetics? - Lee, Daniel H.; Chikazoe, Junichi (Frontiers in Neuroimaging, 2023)
As subjective experiences go, beauty matters. Although aesthetics has long been a topic of study, its research has not claimed interest and progress commensurate with its import. Here we briefly discuss two recent advances, one computational and one neuroscientific, and their pertinence to aesthetic processing. First, we suggest that deep neural networks provide the capacity to model representations essential to aesthetic experiences. Second, we highlight the Principal Gradient as an axis of information processing potentially key to examining where and how aesthetic processing takes place in the brain. In concert with established neuroimaging tools, we suggest these advances may cultivate a new frontier of understanding our aesthetic experiences.